Pain Reduction Techniques to Overcome Back Pain Complaints in Third Trimester of Pregnancy - Sri Maryati; Karwati Karwati; Damai Yanti (Humanistic Network for Science and Technology (HNST), 2022)
The problem that is often experienced by pregnant women in the third trimester is low back pain, it is estimated that around 70% of women complain of some form of low back and back pain at some point in pregnancy, childbirth and post partum. One of the therapy that can be given to mothers with low back pain is acupressure. The purpose of the study was to determine the effect of pain reduction techniques with acupressure to overcome complaints of low back pain in the third trimester of pregnancy. The design of this study was one group pre-test post-test. The sample was taken by accidental sampling, with the research subjects being pregnant women in the third trimester who visited PMB